TANGGUNG JAWAB ORGAN PERSEROAN TERBATAS DALAM KASUS KEPAILITAN - Siti Hapsah Isfardiyana (Arena Hukum, 2014)
AbstractThis paper aims to determine the responsibility of the Company's internal organs, namely the shareholders, Directors and Commissioners, if the Company suffered a loss to not be able to pay its debts to creditors and eventually bankrupted due to improper legal organ of the Company while the Company Indonesia adopts a separate entity and limited liability. However, limited liability can be changed to unlimited liability by piercing the corporate viel abusing his authority when organs Company. Authority Board of Directors and Commissioner based the principle of fiduciary duty. In this study the authors will use the method of normative conceptual approach that moved from the separate entity doctrine, limited liability, fiduciary duty, and piercing the corporate viel to look for suitability in laws and crustaceans. Accountability organs according to the Company's separate entity, limited liability, fiduciary duty, and piercing the corporate viel has been set in the laws and regulations. Each organ can be held accountable if found guilty of negligence or willful misconduct that led to the bankruptcy of the Company. Shareholders applied Article 3 paragraph (2) of the PT, the Board of Directors subject to Article 104 paragraph (2) of the PT, the Commissioner subject to Article 115 Paragraph (1) and paragraph (2) of the PT. Board of Directors and the Commissioner can also be charged with Article 1365 and 1366 of the Civil Code. In addition, the Criminal Code also can ensnare the Board of Directors and Commissioners with Article 398 and 399 of the Criminal Code. Key words: responsibility, organ, bankruptcy Â AbstrakTulisan ini bertujuan untuk mengetahui tanggung jawab organ Perseroan yaitu pemegang saham, Direksi dan Komisaris, apabila Perseroan mengalami kerugian hingga tidak bisa membayar utang-utangnya kepada kreditor dan akhirnya dipailitkan akibat kesalahan organ Perseroan sedangkan hukum Perseroan Indonesia menganut sistem separate entity dan limited liability. Namun tanggung jawab terbatas dapat berganti menjadi tanggung jawab tidak terbatas melalui piercing the corporate viel ketika organ Perseroan menyalahgunakan wewenangnya. Wewenang Direksi dan Komisaris didasarkan prinsip fiduciary duty. Dalam penelitian ini penulis akan menggunakan metode normatif dengan pendekatan konseptual yang beranjak dari doktrin separate entity,limited liability , fiduciary duty, dan piercing the corporate viel untuk dicari kesesuiannya dalam peraturan perundang-udangan. Penelitian menunjukan bahwa pertanggungjawaban organ Perseroan menurut separate entity, limited liability, fiduciary duty, dan piercing the corporate viel telah diatur dalam peraturan perundang-undang. Masing-masing organ dapat dimintai pertanggungjawaban apabila terbukti melakukan kelalaian atau kesengajaan yang menyebabkan Perseroan pailit.Pemegang saham dapat dkenakan Pasal 3 ayat (2) UU PT, Direksi dikenakan Pasal 104Â ayat (2) UU PT, Komisaris dikenakan Pasal 115 Ayat (1) dan Ayat (2)Â UU PT . Direksi dan Komisari juga dapat dikenakan dengan Pasal 1365 dan 1366 KUHPerdata. Selain itu, KUHP juga dapat menjerat Direksi dan Komisaris dengan Pasal 398 dan 399 KUHP. Kata kunci:tanggung jawab, organ, kepailitan